Model Kultur Sekolah Berbasis Multiple Intelligences di SD Inpres Palanro Kabupaten Barru - Kamaruddin Hasan; Abdul Hakim; Fajar Fajar (Publikasi Pendidikan, 2017)
Along with the development of the theory of Multiple Intelligences in the realm of education and learning, it is possible that the renewal in the cultural order of schooling. School as a systematic institution inheritance of the nation's cultural values will undergo changes in accordance with the development of the paradigm of intelligence. The importance of school culture as a place for students to develop a variety of intelligence, it is necessary model of school culture that accommodate the growth of various intelligences of students. The results showed that the school culture model based on multiple intelligence developed in SD Inpres Palanro was valid, practical, and interesting. Furthermore, the use of the school culture model was effective in increasing the activity of teachers and students in SD Inpres Palanro.